Evaluating the hematological and clinical-chemistry parameters of kratom (Mitragyna speciosa) users in Malaysia - Singh, Darshan; Müller, Christian P.; Murugaiyah, Vikneswaran; Hamid, Shahrul Bariyah Sahul; Vicknasingam, Balasingam K.; Avery, Bonnie; Chear, Nelson Jeng Yeou; Mansor, Sharif Mahsufi (Journal of Ethnopharmacology, 2018)
ETHNOPHARMACOLOGICAL RELEVANCE: Kratom (Mitragyna speciosa Korth.) from the Rubiaceae family is an indigenous tropical medicinal tree of Southeast Asia. Kratom leaves have been used for decades in Malaysia and Thailand in traditional context for its perceived vast medicinal value, and as a mild stimulant among manual labourers. Kratom consumption has been reported to cause side-effects in kratom users. AIM OF THE STUDY: To evaluate kratom's effects towards hematological and clinical-chemistry parameters among regular kratom users in Malaysia. METHODS: A total of 77 subjects (n=58 regular kratom users, and n=19 healthy controls) participated in this cross-sectional study. All the surveys were conducted through face-to-face interview to elicit subject's socio-demographic characteristics and kratom use history. A full-blood test was also administered. Laboratory analysis was conducted using GC-MS to determine mitragynine content in the acquired kratom samples in order to relate mitragynine consumption with possible alterations in the blood parameters of kratom users. RESULTS: Findings showed that there were no significant differences in the hematological and clinical-chemistry parameters of traditional kratom users and healthy controls, except for HDL and LDL cholesterol values; these were found to be above the normal reference range for the former. Similarly, long-term kratom consumption (>5 years), and quantity of daily kratom use (≥3 ½ glasses; mitragynine content 76.3-114.8mg) did not appear to alter the hematological and biochemical parameters of kratom users. CONCLUSION: These data suggest that even long-term and heavy kratom consumption did not significantly alter the hematological and clinical-chemistry parameters of kratom users in a traditional setting.
EVALuna2:36549